RNAseq data from 112 samples of benign or malignant ovarian tumours - Uppsala University (FEGA Sweden, 2025)
This dataset contains ~1.2 TB RNA sequencing data in fastq format from 112 samples of fresh-frozen ovarian tumours from a total of 111 women, two samples being replicates. The samples were collected from the U-CAN collection at Uppsala Biobank and include both benign (n = 18) and malignant (n = 94) tumours.
The RNA sequencing samples were sequenced using paired-end sequencing (2x150 bp) on an Illumina NovaSeq 6000 instrument at the SciLifeLab National Genomics Infrastructure (NGI) in Uppsala.

This dataset is 1 of 1 included in the study titled Total RNA expression in benign ovarian and malignant ovarian tumours, http://identifiers.org/ega.study:EGAS50000001045.
Keywords: transcriptomics; cancer; health; human; Genetics and Genomics; Genetik och genomik